Pembelajaran berasaskan aplikasi mudah alih “Kelas Anak Jawi” - Md. Mansor, Abdul Hakim (2021)
This study uses the application "Kelas Anak Jawi" to see the ability of students to write and pronounce Jawi letters, syllables and words. This study involved ten (10) kindergarten students who studied Jawi. The instruments in this study are pre-test, post-test and expert evaluation form. Data were analyzed using means and percentages. The results of this study showed that there was an increase in test scores conducted in assessing students' ability to write and pronounce Jawi letters, syllables and words. In addition, the results of this study also show that there is an increase in students' performance on the mastery of letters, syllables and Jawi words. In conclusion, the use of the application "Kelas Anak Jawi" has been able to improve students' abilities in writing and pronouncing Jawi letters, syllables and words well.